Previously undiagnosed serotonin toxicity: from pre-anaesthetic assessment to postoperative management – a case report - Bianca-Liana Grigorescu; Irina Saplacan; Mihai Raul Morariu (Journal of the Pakistan Medical Association, 2022)
Serotonin syndrome (SS), also known as serotonin toxicity, is a life-threatening condition induced by certain drugs that affect serotonin metabolism. We report a case of SS, induced by a combination of three drugs encountered in a patient with a previously suspected allergy to metoclopramide and pitofenone discovered as an "anaesthetic incident”. In the immediate postoperative period, following the administration of antiemetic and analgesic treatment, the patient presented generalized myoclonus and intense abdominal pain. The diagnosis of SS was established using the Hunter Criteria. After the discontinuation of potentially triggering medication and anticonvulsant therapy, the patient was discharged from the ICU with complete resolution within six days. Given the increased use in clinical practice of drugs that may interfere with serotonin metabolism, the rising prevalence of mental health and the increasing use of illicit drugs, it is essential for anaesthetists to be aware of the potential for SS occurrence. Continue...